KISAH KESENGSARAAN TUHAN KITA YESUS KRISTUS MENURUT YOHANES - Berthold Anton Pareira (Studia Philosophica et Theologica, 2002)
This is a reading on the theology of the Passion of our Lord Jesus Christ according to John. It is a narrative theology and therefore must be listened by the believing communities as narrative. Jesus is the Lord of His Passion. His is doing the will of the Father. He is King of the Truth rejected by the Jews. His death is the birth of a new community and the source of its life. The author concludes his study with a short reflection on this great theology of the Passion for the Church. pendidikan. Oleh karena itu apa yang dikatakan Paulo Freire dan Illich dapat dibenarkan. Antara lain mereka mengatakan bahwa pendidikan yang selama ini dianggap sakral dan penuh kebajikan ternyata mengandung juga penindasan.